Amyand’s hernia in a 3-month-old infant: A case report - Samia Obilat; Soumya El Graini; Nazik Allali; Latifa Chat; Loubna Aqqaoui; Fouad Ettayebi; Siham El Haddad (SAGE Open Medical Case Reports, 2024)
Amyand’s hernia is a rare condition characterized by an inguinal hernia containing the appendix, which can lead to complications. It is more common in children and it can be challenging to diagnose due to its location, often being mistaken for other conditions like strangulated hernias, orchitis-epididymitis, or testicular torsion. Imaging, including computed tomography and sonography, plays an important role in diagnosis, which is usually made intraoperatively. A case concerning a 3-month-old boy with a large acute scrotum that had been evolving for 4 days was presented. Clinical examination revealed a hard inguinal mass and a large scrotum with signs of inflammation. An inguinoscrotal ultrasound found a herniated appendix, suggesting the diagnosis of Amyand’s hernia, which was confirmed after surgery.